Gamma-beam generation at the synchrotron "Pakhra" by resonance excitation of accelerated electrons - Bashmakov, Yu.A.; Karpov, V.A. (Вопросы атомной науки и техники, 2012)
System of homogeneous extraction of gamma-beam from the 1.2 GeV electron synchrotron "Pakhra" is discussed. Accelerated electrons are slowly brought to the tungsten target, which is placed inside the synchrotron vacuum chamber. During extraction high frequency voltage on accelerator’s cavity is hold constant. Limited electron betatron oscillations are exiting by means of the gradient and the octupole pole face windings. Time uniformity of gamma quanta flow is provided by a special choice of the time dependence of the index of the synchrotron guide magnetic field. Control of the extraction process by a computer with usage of a feedback circuit will be performed.